The Perspective of Fifth and Sixth Year Dental Students of Zahedan University of Medical Sciences about Practical Training and Related Factors - Nahid Ramazani; Mohsen Ramazani; Abdolhakim Fazeli (Kerman University of Medical Sciences, 2014)
Background & Objective: Considering student input is a key component of dental education process The objective of this study was to evaluate the last two years students perspectives about practical training at Zahedan Dental School Iran and related factors in the academic year 201112   Methods: In this descriptive analytical study 108 fifth and sixth semester students of Zahedan Dental School participated who were selected by census method The modified clinical education instructional quality questionnaire (with confirmed validity and reliability) was distributed among students at the second half of all courses in first semester of 201112 academic year and each of students recorded his or her own perspective about the presented educational department The questionnaire consisted of clinical learning opportunities learned practical activities and interaction with clinical instructors The minimum and maximum scores of each part and the total questionnaire were 1 and 5 respectively Mean scores were calculated based on the Likert scale rating The data were analyzed using oneway ANOVA and independent samples test at the significant level 005   Results: The mean total students perspective score was 348 ± 087 of the maximum of 5 The highest mean perspective scores belonged to interaction with clinical instructors and clinical learning opportunities respectively The mean of total perspective score of fifthyear students was significantly higher than that of the sixthyear students (P = 0032) There was also significant differences in mean total score of students perspective in respect to age gender and grade point average (GPA) (P = 0048 P = 0040 and P =0037 respectively)   Conclusion: Students reported practical training as relatively favorable Students perspectives also determined the weakness and strength points of practical training